Perspectives on the electrically induced properties of electrospun cellulose/liquid crystal devices - Rosu, C. (2012)
A mat of electrospun cellulose fibers are deposed on transparent conductive oxide covered glass, and two such plates enclose a nematic liquid crystal. Thus two new types of Cellulose based Polymer Dispersed Liquid Crystal devices, based on hydroxypropylcellulose and Cellulose Acetate and the nematic liquid crystal E7 have been obtained. The current-voltage characteristics indicates ionic type conduction. Heating-cooling cycles have been applied on the samples and the activation energies have been determined. Simultaneously with the thermo-stimulated currents, the optical transmission dependence on the d.c. electric field and temperature was registered. ON-OFF switching times have been determined for different control voltages. (C) 2011 Elsevier B.V. All rights reserved.